The spatial effect of fiscal decentralisation on regional disparities: the case from Indonesia - Adiwan F. Aritenang (Indonesian Journal of Geography, 2014)
This study investigates the effect of decentralization on regional economic convergence between 1994 and 2004. Using spatial analysis, this research explains the presence of spatial dependence, which it is misleading to ignore it on the common linear regression. The paper argues that there is a strong evidence of spatial autocorrelation among.Indonesia districts and regional convergence rate is higher in the decentralization period. Furthermore, the spatial error model suggested that, despite Jakarta’s major economic and political role, a random shock is insignificant if it introduced to the capital city.